Sustainable city logistics: rebound effects from self-driving vehicles - Jasmin Mol̈ler; Kateryna Daschkovska; Ronald Bogaschewsky (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: This paper investigates direct and indirect rebound effects caused by the implementation of different types of car driving technologies - electric cars, highautonomous, and fully-autonomous vehicles in the sustainable city environment. Methodology: Lifecycle Assessment analysis extended by the social and economic dimensions has been completed for the aforementioned vehicle types in order to identify, categorize, and systemize the possible negative impacts of the investigated car driving technologies within the local (city logistics) and global (world ecosphere) environment. Findings: Differences between local and global induced negative impacts of the new driving technologies have been identified. The paper compares the most expected/ unexpected rebound effects for the three types of vehicles in the local city logistics environment and under the consideration of global impacts. Originality: The rebound effect is mostly based on energy consumption. In this research, we have identified and analyzed indirect rebound effects from the imminent adoption of self-driving vehicles that are relevant to either city logistics development or the global environmental system.
urn:nbn:de:gbv:830-882.054890; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Rebound effect; Sustainability; Autonomous vehicles; Life cycle